A unique case of Fusobacterium nucleatum spondylodiscitis communicating with a pleural empyema through a fistula. Issue 11 (9th September 2021) - Bonnesen, Barbara; Sivapalan, Pradeesh; Naghavi, Hadi; Back Holmgaard, Dennis; Sloth, Carsten; Wiese, Lothar; Kolekar, Shailesh
Abstract : Species (spp.) belonging to the genus Fusobacterium are anaerobic commensals colonizing the upper respiratory tract, the gastrointestinal tract, and the genitals. Infections with Fusobacterium spp. have been reported at many anatomical sites, including pneumonias and pleural empyemas; however, there are very few published cases of Fusobacterium spp. causing spondylodiscitis or fistulas. Bone infections with Fusobacterium can spread directly to surrounding muscular tissue or by hematogenous transmission to any other tissue including pleurae and lungs. Similarly, pleural infections can spread Fusobacterium spp. to any other tissue including fistulas and bone. Concomitant pleural empyema and spondylodiscitis are rare; however, there are a few published cases with concomitant disease, although none caused by Fusobacterium spp. A 77‐year‐old female patient was assessed using computed tomography (CT) scanning of the thorax and abdomen, as well as analyses of fluid drained from the region affected by the pleural empyema. A diagnosis of Fusobacterium empyema, fistula, bacteremia, and spondylodiscitis was made, and the patient's condition improved significantly after drainage of the pleural empyema and relevant long‐term antibiotic treatment. We describe the first confirmed case with concomitant infection with Fusobacterium nucleatum as spondylodiscitis and pleural empyema connected by a fistula.